Uncontaminating Concrete Mix Using Sugarcane Bagasse Ash: A Review on its Hardened Properties. Issue 1 (January 2021) - Philip, R B; Das, G N; Kuriakose, S K; Jacob, D; Prabha, A S
Abstract: Concrete is one among the most used material for construction other than water. Cement is the important constituent of concrete. During the production of cement high amount of carbon dioxide is emitted and is responsible for global warming. High amount of cement production is causing environmental problem. Use of agro-waste materials like bagasse ash, increases the strength characteristics of concrete and also causes proper disposal of the waste materials. In this paper, use of sugarcane bagasse ash, an agro-waste product, as a partial replacement of the cement in concrete mix and its effect on the strength parameters of concrete are also identified on the basis of compressive strength, spilt tensile strength and flexural strength. This waste usage is very economical and also have positive impacts on minimizing environmental pollutions.